Doctor's orders ; Greening of the Philippines ; Die hard (Fans) [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Discusses the medical malpractice cases; environmental consciousness among Filipinos and the adulation of fans to their idols.